2020
DOI: 10.3389/fphys.2020.585667
|View full text |Cite
|
Sign up to set email alerts
|

Pain Across the Menstrual Cycle: Considerations of Hydration

Abstract: Chronic pain – pain that persists for more than 3 months – is a global health problem and is associated with tremendous social and economic cost. Yet, current pain treatments are often ineffective, as pain is complex and influenced by numerous factors. Hypohydration was recently shown to increase ratings of pain in men, but studies in this area are limited ( n = 3). Moreover, whether hypohydration also affects pain in women has not been examined. In women, changes in the concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…In studies of the relationship between menstrual cycle subphases and pain perception in healthy females, the definition of menstrual subphase is important ( 42 ). Many studies did not verify the menstrual phase by confirming that the participants had ovulated but only simply counted days starting with the first day of menses ( 43 47 ); this fails to account for the wide variability in menstrual cycle duration and does not confirm that ovulation has occurred ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the relationship between menstrual cycle subphases and pain perception in healthy females, the definition of menstrual subphase is important ( 42 ). Many studies did not verify the menstrual phase by confirming that the participants had ovulated but only simply counted days starting with the first day of menses ( 43 47 ); this fails to account for the wide variability in menstrual cycle duration and does not confirm that ovulation has occurred ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the effects of hydration on pain perception have also been reported, and hydration may also be linked to changes in the phases of the menstrual cycle ( 42 , 56 , 57 ). This study mainly observed the correlation between changes in sex hormones and changes in pain threshold but not including hydration in the analysis, which is also one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, despite adequate power for the present analyses as determined per our power analysis, our modest sample size prevented us from additionally controlling for menstrual cycle phase and hormonal factors (e.g., birth control). Given well established differences in pain and affect across the menstrual cycle, [38][39][40][41] menstrual cycle-related variability is a vital consideration for future research aimed to characterize contributors to perceived opioid benefit. Finally, the perceived opioid benefit questionnaire is not yet a validated measure; psychometric studies verifying the internal consistency and test-retest reliability of this novel measure will provide an asset to future research examining opioid benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Water is necessary for the development of life and survival [1,8,10,13,24], this is its participation in metabolism, facilitation of cellular metabolism [3,22], modulation of normal osmotic pressure, maintenance of electrolyte balance, regulation of body temperature and many others physiological processes [9,19,23]. It has been proven that both excessive and insufficient water consumption has a negative effect on the health of our body [2,11,14,26,28].…”
Section: Introductionmentioning
confidence: 99%